Clinical and Prognostic Impact of a New Left Ventricular Ejection Index in Primary Mitral Regurgitation Because of Mitral Valve Prolapse - Magne, Julien; Szymanski, Catherine; Fournier, Alexandre; Malaquin, Dorothée; Avierinos, Jean Francois; Tribouilloy, Christophe (Circulation. Cardiovascular imaging, 2015)
To prevent left ventricular dysfunction (LVD), surgery is recommended in patients with severe primary mitral regurgitation as soon as ejection fraction (EF) ≤60% or LV end-systolic diameter ≥40 mm. However, LVD may be concealed behind preoperative normal LVEF and LV end-systolic diameter. We sought to identify whether a new composite echocardiographic Doppler marker of the LV ejection according to the LV dilatation may predict postoperative LVD and outcome after mitral valve repair in patients with primary mitral regurgitation. Between 1991 and 2010, patients who underwent mitral valve repair for primary mitral regurgitation were studied. From preoperative echocardiography, we calculated LV ejection index (LVEI) using following formula: LVEI=indexed LV end-systolic diameter/LV outflow tract time-velocity integral. In the 278 patients included, the best correlation with postoperative LVEF was found with LVEI (r=-0.40; P<0.0001), even in patients with preoperative LVEF≥60% (r=-0.46; P<0.0001). In multivariable analysis, LCEI>1.13 was an independent predictor of postoperative LVD (P<0.0001). During a mean follow-up of 10±4.6 years, 67 (29%) deaths occurred. When compared with patients with preserved LVEI, those with LVEI>1.13 had significantly lower both survival and cardiac death-free survival (P=0.017 and P=0.008, respectively). Similar results were found in patients with preoperative LVEF≥60% (P=0.049 and P=0.016, respectively). In Cox proportional hazard model, after meticulous adjustment for cofactors, LVEI>1.13 remains independently associated with death (hazard ratio, 1.64; P=0.039) and cardiac-related death (hazard ratio, 3.27; P=0.026). After mitral valve repair for primary mitral regurgitation, the preoperative LVEI is a new and simple composite parameter of both LV dilatation and LV forward flow able to accurately predict postoperative LVD and outcome.